2020
DOI: 10.1007/s10902-020-00324-7
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone-Based Ecological Momentary Assessment of Well-Being: A Systematic Review and Recommendations for Future Studies

Abstract: Feelings of well-being and happiness fluctuate over time and contexts. Ecological Momentary Assessment (EMA) studies can capture fluctuations in momentary behavior, and experiences by assessing these multiple times per day. Traditionally, EMA was performed using pen and paper. Recently, due to technological advances EMA studies can be conducted more easily with smartphones, a device ubiquitous in our society. The goal of this review was to evaluate the literature on smartphone-based EMA in well-being research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
112
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(147 citation statements)
references
References 148 publications
7
112
1
Order By: Relevance
“…Furthermore, most mobile sensing research is based on WEIRD samples. Figure 1 maps the locations of smartphone-based passive sensing studies included in the reviews on health and well-being from Cornet and Holden (2018) and on well-being from de Vries et al (2021). An overview of the included studies and samples can be found in Table 1, and a detailed list can be found on this project's OSF page (https://osf.io/2wbda/).…”
Section: The State Of Cross-cultural Mobile Sensing Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, most mobile sensing research is based on WEIRD samples. Figure 1 maps the locations of smartphone-based passive sensing studies included in the reviews on health and well-being from Cornet and Holden (2018) and on well-being from de Vries et al (2021). An overview of the included studies and samples can be found in Table 1, and a detailed list can be found on this project's OSF page (https://osf.io/2wbda/).…”
Section: The State Of Cross-cultural Mobile Sensing Researchmentioning
confidence: 99%
“…Mobile Sensing Study Locations Around the World Note. World map depicting the locations and sample sizes of k = 60 passive sensing studies listed in two reviews (Cornet & Holden, 2018;de Vries et al, 2021). Studies that did not use passive sensing (k = 27) were excluded.…”
Section: Figurementioning
confidence: 99%
“…A recent review that addressed diurnal variations of well-being measures reported mixed results. Some studies showed increases in mood valence and calmness during the day whilst others did not (see de Vries et al 2020).…”
Section: Mood Dynamics During Lockdownmentioning
confidence: 99%
“…The analysis also pursued a secondary aim to demonstrate that data collected by a smartphone with an EMA tool in daily rhythm can be a basis for meaningful analyses of the formation and change of emotions toward a phenomenon such as the COVID-19 pandemic. EMA was developed to study mood management and has typically been applied by paper and pencil before the ubiquity of the smartphone [35][36][37][38]. Respondents are contacted by EMA, with contacts serving as a reminder that a questionnaire is due, as a device to place the time of the interview at a particular hour of the day, or in juxtaposition to particular events.…”
Section: Ema Designmentioning
confidence: 99%